SISTEM DETEKSI DIABETES BERBASIS ANDROID MENGGUNAKAN METODE FUZZY INFERENCE SYSTEM - Agus Junaidi (LPPM Universitas Bina Sarana Informatika, 2011)
Lifestyle because of high income, fast-food restaurant dishes, and the current lack of exercise has increased the risk of someone suffering from degenerative diseases such as diabetes mellitus or better known as diabetes. To further facilitate the public in knowing the disease diabetes need to be made a software that can detect the disease early to prevent diabetes complications can be fatal as blindness and foot rot (gangrene). Android-based diabetes detection system works using the fuzzy inference system that includes fuzzification process, the process of inference, and the process of using the centroid method defuzzification / center of Grafity. In reading the data is inputted in accordance with predetermined criteria, namely age, weight and height to calculate body mass index, blood pressure and the resulting output will be the risk of diabetes. When this has been the android operating system on a cellular phone users continues to be increase, with applications android-based diabetes detection system will automatically allows users to always check the health condition anytime and anywhere. Key word : diabetes, android, fuzzy inference system